Coopération et contrebande de drogue dans les parcs co-frontaliers du nord-ouest américain (Massif des Cascades) - Caroline Moumaneix (L'Espace Politique)
Since the 1990’s, drug smuggling has been spreading in the co-border parks between British Columbia (Canada) and Washington State (United States). One of the main reasons to explain this growing phenomenon is that the border line between these border protected areas is less watched over than elsewhere. The two bordering States have thus elaborated a security cooperation to fight against this smuggling, in particular with the Integrated Border Enforcement Team (IBET), including the co-border parks. These joint teams have first been experimented in the Cascades since 1996 before being generalized to the entire border line between Canada and the US through the Smart Border Declaration after 9/11. The IBET are leading efficient operations on the field, like the Frozen Timber/E-Printer one in the Cascades (2006), but they failed to prevent smugglers to grow marijuana inside these co-border protected areas in which six fields have been discovered in 2008. This example illustrates the building of a surprising security cooperation in an hydrid border region, assembling co-border protected areas, and the question of priority between national security and environment protection. 9/11 may have speeded up an on-going process.